Spectrum of Imaging Findings in Posterior Reversible Encephalopathy Syndrome (PRES) from Typical to Atypical: Spectrum of Imaging Findings (GAIMS Journal of Medical Sciences, 2022)
Posterior reversible encephalopathy syndrome (PRES) is a clinico-radiological syndrome characterized by headache, consciousness impairment, seizures, and visual deficits and is associated with white matter changes predominantly affecting the posterior parietal and occipital lobes of the brain. Apart from the above-described typical location of the changes, the most common atypical location involves the brain stem/cerebellar hemispheres and basal ganglia. Additionally, PRES may be complicated in some cases by the presence of cytotoxic edema and haemorrhage.Since magnetic resonance imaging (MRI) is more sensitive and specific imaging technique compared to computerized tomography, establishing the diagnosis and follow-up in patients with PRES is based mainly on MRI findings. It is particularly important not to exclude PRES as a possible diagnosis when we have the appropriate clinical presentation accompanied by the atypical radiological findings, since this clinical-radiological syndrome can often be manifested with an atypical MRI image